Engineering Risk Analysis and Decision for Communities Facing Natural Hazards: A Talk in Four Parts - ICASP14; Corotis, Ross (My University, 2023)
This presentation is the culmination of a decade of research on the technological and social aspects of decision-making for the consideration of natural hazards in communities. It covers four different aspects, and as such, this paper consists of a short summery for each of the four parts, each followed by published references of the author and his graduate students regarding the subject of that part.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED